Resistance Characteristics of Pork Meatballs and Beef Meatballs Using Multimeter - Qodir, Moh. Yasin Faidlul; Rahmaningrum, Nadia; Rakhmadi, Frida Agung (Proceeding International Conference on Science and Engineering, 2019)
Meatballs is food typical Indonesian that has taste delicious. It is even the most referred food for Indonesian people. The ingrediants used in meatballs is meat, flour and etc. Most Indonesian people are Muslim. So, not carelessly eating meatballs made from meat (Pork). The purpose of this study is to find out whether meatballs use pork or not, using the resistance method with a digital multimeter. Resistance is the ability to inhibit electricity. This trial uses pork meatballs and beef meatballs 5 times a try on each meatball. Resistance values were obtained for pork meatballs 3,718 ? and for beef meatballs 2,988 ?. From the data obtained, the resistance value in pork meatballs is higher than beef meatballs.